THE EFFECT OF PERCEIVED ORGANIZATIONAL SUPPORT, MEANING OF WORK AND PROACTIVE PERSONALITY ON EMPLOYEE CREATIVITY (STUDY ON EMPLOYEES OF HARNO SURYA NGEMPLAK BOTHI) - Krisminanti Agustina; Putri Maisara (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
This study aims to determine the effect of perceived organizational support, work meaning and proactive personality on employee creativity. The results of data analysis in this study are that there is an influence of Perceived Organizational Support on Employee Creativity, there is an influence of Job Meaning on Employee Creativity and there is an influence of Proactive Personality on Employee Creativity, and also from the results of the F test analysis, the results show that Perceived Organizational Support, Work Meaning and Personality Proactive jointly affects Employee Creativity. Another result of this study is that the coefficient of determination (R2) produces a value of 0.59 or 59%. This means that 59% of employee creativity in Harno Surya Ngemplak Bothi Kartasura employees is influenced by the variables of Organizational Support Perception, Work Meaning and Proactive Personality while the remaining 41% is influenced by other variables not examined in this study. Keywords: Perceived Organizational Support, Meaning Of Work, Proactive Personality, Employee Creativity